Development of Learning Applications e Mole B in Badminton Games - Boby Agustan; Ramdhani Rahman (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
The lack of technology-based learningmedia in badminton activities has motivated researchers to develop new technology-based learning media. This media is designed to be user-friendly, making it easy to operate and practice anywhere. This study aimed to develop an electronic-based badminton learning application called "E-Mole B." The research utilizes the research and development or R&D method. Product trials were carried out at SMPN 4 Ciawigebang. With a small sample size of 10 extracurricular student respondents and a large scale test of 35grade 7 student respondents at SMPN 4 Ciawigebang. The results of this research are based on a small-scale test of 85% in the "feasible" category and a large-scale test of 87.50% in the "feasible" category